Design, synthesis, and biological evaluation of novel halogenated chlorido[N,N′-bis(salicylidene)-1,2-bis(3-methoxyphenyl)ethylenediamine]iron(III) complexes as anticancer agents - Astrid Dagmar Bernkop-Schnürch; Klaus Huber; Armida Clauser; Monika Cziferszky; Daniel Leitner; Heribert Talasz; Martin Hermann; Stephan Hohloch; Ronald Gust; Brigitte Kircher (JBIC Journal of Biological Inorganic Chemistry, 2024)
Iron(III) complexes based on N,N ´-bis(salicylidene)ethylenediamine (salene) scaffolds have demonstrated promising anticancer features like induction of ferroptosis, an iron dependent cell death. Since poor cellular uptake limits their therapeutical potential, this study aimed to enhance the lipophilic character of chlorido[ N,N ′-bis(salicylidene)-1,2-bis(3-methoxyphenyl)ethylenediamine]iron(III) complexes by introducing lipophilicity improving ligands such as fluorine ( X1 ), chlorine ( X2 ) and bromine ( X3 ) in 5-position in the salicylidene moieties. After detailed characterization the binding to nucleophiles, logP values and cellular uptake were determined. The complexes were further evaluated regarding their biological activity on MDA-MB 231 mammary carcinoma, the non-tumorous SV-80 fibroblast, HS-5 stroma and MCF-10A mammary gland cell lines. Stability of the complexes in aqueous and biological environments was proven by the lack of interactions with amino acids and glutathione. Cellular uptake was positively correlated with the logP values, indicating that higher lipophilicity enhanced cellular uptake. The complexes induced strong antiproliferative and antimetabolic effects on MDA-MB 231 cells, but were inactive on all non-malignant cells tested. Generation of mitochondrial reactive oxygen species, increase of lipid peroxidation and induction of both ferroptosis and necroptosis were identified as mechanisms of action. In conclusion, halogenation of chlorido[ N,N ′-bis(salicylidene)-1,2-bis(3-methoxyphenyl)ethylenediamine]iron(III) complexes raises their lipophilic character resulting in improved cellular uptake. Graphical abstract

Rho-inhibiting C2IN-C3 fusion toxin inhibits chemotactic recruitment of human monocytes ex vivo and in mice in vivo - Tobias Martin; Amelie Möglich; Ina Felix; Christina Förtsch; Anne Rittlinger; Annette Palmer; Stephanie Denk; Julian Schneider; Lena Notbohm; Mona Vogel; Hartmut Geiger; Stephan Paschke; et al. (Archives of Toxicology, 2018)

K+ channel signaling in irradiated tumor cells - Benjamin Stegen; Lukas Klumpp; Milan Misovic; Lena Edalat; Marita Eckert; Dominik Klumpp; Peter Ruth; Stephan M. Huber (European Biophysics Journal, 2016)

Kv3.4 potassium channel-mediated electrosignaling controls cell cycle and survival of irradiated leukemia cells - Daniela Palme; Milan Misovic; Evi Schmid; Dominik Klumpp; Helmut R. Salih; Justine Rudner; Stephan M. Huber (Pflügers Archiv - European Journal of Physiology, 2013)

Decreased Redox-Sensitive Erythrocyte Cation Channel Activity in Aquaporin 9-Deficient Mice - Yuliya V. Kucherenko; Stephan M. Huber; Søren Nielsen; Florian Lang (The Journal of Membrane Biology, 2012)

Functional significance of the intermediate conductance Ca2+-activated K+ channel for the short-term survival of injured erythrocytes - Michael Föller; Diwakar Bobbala; Saisudha Koka; Krishna M. Boini; Hasan Mahmud; Ravi S. Kasinathan; Ekaterina Shumilina; Kerstin Amann; Golo Beranek; Ulrike Sausbier; Peter Ruth; Matthias Sausbier; et al. (Pflügers Archiv - European Journal of Physiology, 2010)

Enhanced eryptosis of erythrocytes from gene-targeted mice lacking annexin A7 - Elisabeth Lang; Philipp A. Lang; Ekaterina Shumilina; Syed M. Qadri; Yuliya Kucherenko; Daniela S. Kempe; Michael Föller; Anna Capasso; Thomas Wieder; Erich Gulbins; Christoph S. Clemen; Claudia Herr; et al. (Pflügers Archiv - European Journal of Physiology, 2010)

Increased Cation Conductance in Human Erythrocytes Artificially Aged by Glycation - Yuliya V. Kucherenko; Shefalee K. Bhavsar; Valentin I. Grischenko; Uwe R. Fischer; Stephan M. Huber; Florian Lang (The Journal of Membrane Biology, 2010)

The Plasmodium falciparum-induced anion channel of human erythrocytes is an ATP-release pathway - Canan Akkaya; Ekaterina Shumilina; Diwakar Bobballa; Verena B. Brand; Hasan Mahmud; Florian Lang; Stephan M. Huber (Pflügers Archiv - European Journal of Physiology, 2009)

Inhibition of eryptosis and intraerythrocytic growth of Plasmodium falciparum by flufenamic acid - Ravi S. Kasinathan; Michael Föller; Saisudha Koka; Stephan M. Huber; Florian Lang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Inhibition of erythrocyte “apoptosis” by catecholamines - Philipp A. Lang; Daniela S. Kempe; Ahmad Akel; Barbara A. Klarl; Kerstin Eisele; Marlies Podolski; Tobias Hermle; Olivier M. Niemoeller; Philipp Attanasio; Stephan M. Huber; Thomas Wieder; Florian Lang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Permselectivity and pH-dependence of Plasmodium falciparum-induced anion currents in human erythrocytes - Christophe Duranton; Valerie Tanneur; Verena Brand; Ciprian D. Sandu; Canan Akkaya; Stephan M. Huber; Florian Lang (Pflügers Archiv - European Journal of Physiology, 2005)

Channel-induced apoptosis of infected host cells?the case of malaria - Florian Lang; Philipp A. Lang; Karl S. Lang; Verena Brand; Valerie Tanneur; Christophe Duranton; Thomas Wieder; Stephan M. Huber (Pflügers Archiv - European Journal of Physiology, 2004)

Cation channels, cell volume and the death of an erythrocyte - Florian Lang; Karl S. Lang; Thomas Wieder; Svetlana Myssina; Christina Birka; Philipp A. Lang; Stephanie Kaiser; Daniela Kempe; Christophe Duranton; Stephan M. Huber (Pflügers Archiv - European Journal of Physiology, 2003)

Chloride conductance and volume-regulatory nonselective cation conductance in human red blood cell ghosts - Stephan M. Huber; Nikita Gamper; Florian Lang (Pflügers Archiv - European Journal of Physiology, 2001)

Inverse regulation of vascular endothelial growth factor and VHL tumor suppressor gene in sporadic renal cell carcinomas is correlated with vascular growth: an in vivo study on 29 tumors - Jürgen Brieger; Eberhard J. Weidt; Peter Schirmacher; Stephan Störkel; Christoph Huber; Jochen H. Decker (Journal of Molecular Medicine, 1999)

Bradykinin-stimulated Cl - secretion in T84 cells. Role of Ca 2+ -activated hSK4-like K + channels - Stephan M. Huber; Johannes Tschöp; Gerald S. Braun; Wolfram Nagel; M. F. Horster (Pflügers Archiv - European Journal of Physiology, 1999)

Expression of the epithelial sodium channel (ENaC) during ontogenic differentiation of the renal cortical collecting duct epithelium - Stephan M. Huber; Gerald S. Braun; Michael F. Horster (Pflügers Archiv - European Journal of Physiology, 1999)

Epithelial nephrogenesis - M. Horster; Stephan Huber; Johannes Tschöp; Gregor Dittrich; Gerald Braun (Pflügers Archiv - European Journal of Physiology, 1997)